8 - African Universities and the Challenge of Research Capacity Development: Akilagpa Sawyerr - Akilagpa Sawyerr, (Journal of Higher Education in Africa, 2003)
Critical for Africa’s future is strengthening indigenous educational systems and institutions for generating and applying knowledge by assuring long-term public support with emphasis on research capacity. In addition to individual skills developed in research work, research capacity includes: quality of the research environment, funding, adequate infrastructure, research incentives, time available to the researcher, etc. In most African countries, conditions for research have been severely compromised as manifest by the generally poor remuneration, heavy teaching loads, inability to mentor young faculty, and in- adequate infrastructure. While the adequacy of public funding is a crucial con- dition, there are a number of concrete programmatic initiatives that could be taken by the higher education and research institutions themselves. These in- clude strengthening of graduate study, improvements in the management of research, provision of a “soft landing ” for young faculty, identification and concentration on “areas of strength, ” and pooling resources with other institu- tions. Special initiatives aimed at individual research capacity development include the Study Programme for Higher Education Management of the Asso- ciation of African Universities (AAU); the Working Groups and Institutes of the Council for the Development of Social research in Africa (CODESRIA); and the work of the National Mathematics Centre of Nigeria.